Law & politics of Brexit - Fabbrini,Federico,Ed (OUP, 2017)
The decision by the people of the United Kingdom to vote in a referendum in June 2016 to leave the European Union has produced shock waves across Europe and the world. Brexit calls into question consolidated assumptions on the finality of the EU, and simultaneously sparks new challenges. These new challenges are not only in regard of the constitutional settlements reached in the UK, notably in Scotland and Northern Ireland, but also on the future of European integration. Now that Article 50 of the Treaty on the European Union has been invoked, and the path towards full withdrawal by the UK from the EU remains clouded in uncertainties, a comprehensive legal and political analysis of how Brexit impacts on UK and the EU appears of the utmost importance. This book brings together leading lawyers, economists and political scientists to discuss the constitutional implications of Brexit and propose possible solutions for the way forward. The book is structured around four main themes. First, it considers how Brexit will be implemented legally and politically, in terms of the withdrawal and the possible new relations between the UK and the EU. Second, it examines the implications of Brexit on the constitutional structure of the UK, as well as on the status of Northern Ireland and the relations with the Republic of Ireland. Third, it examines the implications of Brexit on the constitutional structure of the EU, focusing on a number of key areas of EU policy-making, notably the Area of Freedom Security and Justice, the Single Market, and Economic and Monetary Union. Fourth and finally, the book looks into the mid to long term future, and discusses the prospects for relaunching the EU after and beyond Brexit.